Antibacterial flame-retardant polyester color master batch and preparation method thereof
By using the first and second-level coating, adsorption and composite steps in the preparation of polyester masterbatches, the problem of poor antibacterial and flame retardant properties of polyester products is solved, and the effect of improving the product's antibacterial properties, flame retardant properties, mechanical properties and color fastness is achieved, while avoiding the problem of uneven coloring.
Patent Information
- Application Number
- CN202411347193.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-11
AI Technical Summary
The antibacterial and flame retardant properties of existing polyester products are poor, and the dispersion is poor when directly added to antibacterial and flame retardant is poor, which affects the mechanical properties and color uniformity of the product.
A method of preparing antibacterial flame retardant polyester color masterbatch is adopted to prepare flame retardant and antibacterial agent through the steps of primary and secondary coating, adsorption and composite, to improve their dispersion and compatibility, and mix them with the polyester color masterbatch to form an efficient antibacterial flame retardant polyester color masterbatch.
It improves the antibacterial properties, flame retardant properties, mechanical properties and color fastness of polyester products, avoids the problem of uneven coloring, and improves the filtration performance of color masterbatches.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester masterbatch, and in particular to an antibacterial and flame-retardant polyester masterbatch and a preparation method thereof. Background Art
[0002] Polyester is a polymer formed by the polycondensation of polyols and polyacids. It is a high-performance, widely used polymer material. Polyester has excellent mechanical properties, chemical resistance, heat resistance, and insulation properties.
[0003] Polyester is mainly used to produce fibers, films, and plastic products. Polyester fiber is an important type of synthetic fiber and is mainly used for clothing. Polyester film has high strength, good dimensional stability, and excellent chemical resistance and dielectric properties. It is mainly used to produce packaging materials, screen protectors, etc. Polyester plastic products have excellent impact resistance and chemical resistance and are mainly used to produce beverage bottles, electrical products, building materials, etc.
[0004] A masterbatch, also known as a pigment preparation, is a specialized colorant for polymer materials, primarily used in fibers, films, and plastic products. Composed of three basic elements: pigment, carrier, and additives, a masterbatch is a pigment concentrate formed by uniformly enclosing a large amount of pigment in a resin. Therefore, the tinting strength of a masterbatch is greater than that of the pigment itself. During processing, a small amount of masterbatch can be blended with uncolored resin to achieve the desired pigment concentration. Masterbatches are categorized as specialized and general-purpose. Dedicated masterbatches are manufactured using the same plastic as the carrier, tailored to the customer's specific plastic type. General-purpose masterbatches use a specific resin (usually low-melting-point polyethylene) as the carrier and can be used to color other resins. General-purpose masterbatches have poor coloring properties and can also affect the mechanical properties of the product. Therefore, specialized masterbatches are currently the most commonly used.
[0005] Therefore, when applied to polyester products, specifically polyester fibers, polyester films, and polyester plastic products, the carrier of the masterbatch used is primarily polyester. Furthermore, given the inherently poor antibacterial and flame retardant properties of polyester, if antibacterial agents and flame retardants are directly added during the preparation of polyester products, their poor dispersibility will affect their antibacterial and flame retardant effects, as well as the mechanical properties of the polyester products. Experiments have shown that adding antibacterial agents and flame retardants to the preparation of polyester masterbatch, to produce polyester masterbatch with antibacterial and flame retardant properties, can improve their dispersibility.
[0006] However, in actual production, it was found that the polyester masterbatch with antibacterial and flame retardant effects prepared by antibacterial agents and flame retardants has the following problems: First, considering the poor heat resistance of organic antibacterial agents and organic flame retardants, the use of inorganic antibacterial agents and inorganic flame retardants is also a better choice. The inorganic antibacterial agents and inorganic flame retardants are added in the form of inorganic powder, but the inorganic powder is easy to agglomerate. When preparing polyester masterbatch and using polyester masterbatch to prepare polyester products, there is agglomeration problem, which affects the mechanical properties of the obtained polyester product; Second, inorganic antibacterial agents and inorganic flame retardants have an adsorption effect on pigments. Due to the poor dispersibility of inorganic antibacterial agents and inorganic flame retardants, the pigments will be unevenly dispersed, resulting in uneven coloring of polyester products; Third, inorganic antibacterial agents and inorganic flame retardants have a weak fixing effect on pigments, which will lead to reduced color fastness of polyester products; Fourth, inorganic antibacterial agents and inorganic flame retardants will also affect the filtration performance of polyester masterbatch. Summary of the Invention
[0007] In response to the shortcomings of the existing technology, the present invention provides an antibacterial and flame-retardant polyester masterbatch and a preparation method thereof. The prepared antibacterial and flame-retardant polyester masterbatch can improve the antibacterial properties, flame retardant properties, mechanical properties, and color fastness of polyester products. The polyester masterbatch has good filtration performance and can also avoid the problem of uneven coloring in polyester products.
[0008] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows: A method for preparing an antibacterial flame-retardant polyester masterbatch comprises the following steps: preparing a flame retardant, preparing an antibacterial agent, and mixing; The flame retardant preparation comprises the following steps: primary coating, secondary coating, adsorption, and compounding; The first-level coating comprises mixing nano-magnesium hydroxide and water, adding the mixture to an ultrasonic oscillator, and ultrasonically oscillating the mixture at a power of 800 W for 20-30 minutes at room temperature to obtain a magnesium hydroxide suspension; then adding the mixture to a reactor with sodium alginate, stirring the mixture at a temperature of 70-80° C. at a stirring speed of 300-500 rpm for 40-50 minutes, adding the mixture to a centrifuge, and centrifuging the mixture at a speed of 10,000-11,000 rpm for 15-20 minutes, adding the precipitate to a freeze dryer, and freeze-drying the mixture at -45° C. to -40° C. for 28-32 hours to obtain the first-level coated magnesium hydroxide; In the primary coating, the mass volume ratio of nano magnesium hydroxide, water, and sodium alginate is 50-55g:2000-2200mL:7-8g; The particle size of the nano magnesium hydroxide is 100 nm; The secondary coating comprises mixing the primary coated magnesium hydroxide and water, adding the mixture to an ultrasonic oscillator, and ultrasonically oscillating the mixture at a power of 800 W for 20-30 minutes at room temperature to obtain a coated magnesium hydroxide suspension; adding a calcium chloride aqueous solution to a reactor, stirring the mixture at a stirring speed of 300-500 rpm at 20-40° C., and simultaneously adding all the above-mentioned coated magnesium hydroxide suspension dropwise to the reactor, continuing stirring for 3-4 hours after the addition is completed, adding the mixture to a centrifuge, and centrifuging the mixture at a centrifugal speed of 9000-10000 rpm for 15-20 minutes, washing the precipitate with water for 3-4 times, and then adding the mixture to a vacuum oven and vacuum drying the mixture at 70-80° C. for 8-10 hours to obtain the secondary coated magnesium hydroxide; In the secondary coating, the mass volume ratio of the primary coating magnesium hydroxide, water, and calcium chloride aqueous solution is 50-52g:500-520mL:1900-2100mL; The concentration of the calcium chloride aqueous solution is 5wt%; The calcium chloride aqueous solution is added at a rate of 15-20 mL / min; The adsorption process comprises adding the secondary coated magnesium hydroxide and water into a reactor, stirring at a stirring speed of 400-600 rpm for 20-30 minutes at room temperature, adding a zinc chloride aqueous solution dropwise, continuing to stir for 20-30 minutes after the addition is completed, adding the solution into a centrifuge, centrifuging at a centrifugal speed of 9000-10000 rpm for 15-20 minutes, washing the precipitate with water for 3-4 times, and then adding the solution into a vacuum oven and vacuum drying the solution at 70-80° C. for 8-10 hours to obtain adsorbed magnesium hydroxide; In the adsorption, the mass volume ratio of the secondary coated magnesium hydroxide, water, and zinc chloride aqueous solution is 30-35 g:700-800 mL:400-500 mL; The concentration of the zinc chloride aqueous solution is 5wt%; The dropping speed of the zinc chloride aqueous solution is 25-30 mL / min; The composite is to add adsorbed magnesium hydroxide and water into a reactor, stir at room temperature at a stirring speed of 400-600 rpm for 20-30 minutes, and then dropwise add a methanol solution of 2-methylimidazole. After the dropwise addition is completed, add an ultrasonic oscillator, ultrasonically oscillate at room temperature at a power of 800 W for 50-60 minutes, add the mixture into a centrifuge, centrifuge at a centrifugal speed of 8000-9000 rpm for 15-20 minutes, wash the precipitate with water 3-4 times, and then add the mixture into a vacuum oven and vacuum dry it at 70-80° C. for 8-9 hours to obtain a flame retardant; In the composite, 32-36 g: 700-800 mL: 580-640 mL of magnesium hydroxide, water, and a 4 wt% methanol solution of 2-methylimidazole are adsorbed; The concentration of the methanol solution of 2-methylimidazole is 4wt%; The dropping speed of the methanol solution of 2-methylimidazole is 25-30 mL / min; The preparation of the antibacterial agent comprises the following steps: preparing zinc oxide sol, coating, primary self-assembly, secondary self-assembly, and tertiary self-assembly; The zinc oxide sol is prepared by adding zinc acetate dihydrate and anhydrous ethanol to a reaction kettle, stirring at 70-75° C. at a stirring speed of 400-600 rpm for 40-50 minutes, adding ethanolamine dropwise, and continuing to stir for 50-60 minutes after the addition is completed, adding polyethylene glycol 400, and continuing to stir for 2-2.5 hours to obtain a nano zinc oxide sol; In the preparation of the zinc oxide sol, the mass volume ratio of zinc acetate dihydrate, anhydrous ethanol, ethanolamine, and polyethylene glycol 400 is 26-27 g: 210-230 mL: 12-14 mL: 3-3.5 g; The ethanolamine was added at a rate of 2-3 mL / min; The coating comprises mixing a nano zinc oxide sol and a sodium dodecylbenzene sulfonate aqueous solution, adding the mixture to an ultrasonic oscillator, ultrasonically oscillating at a power of 500 W for 2.5-3 hours at room temperature, adding the mixture to a vacuum concentrator, concentrating the mixture under reduced pressure at 75-80° C. for 25-30 minutes, adding the mixture to a centrifuge, centrifuging the mixture at a centrifugal speed of 10,000-11,000 rpm for 15-20 minutes, washing the precipitate with water for 3-4 times, and then adding the mixture to a vacuum oven, vacuum drying the mixture at 70-80° C. for 10-11 hours to obtain coated zinc oxide; In the coating, the volume ratio of nano zinc oxide sol and sodium dodecylbenzenesulfonate aqueous solution is 100-110:280-300; The concentration of the sodium dodecylbenzenesulfonate aqueous solution is 5wt%; The primary self-assembly comprises adding coated zinc oxide and polydimethylallyl ammonium chloride aqueous solution into a reaction kettle, stirring at room temperature at a stirring speed of 400-600 rpm for 30-40 minutes, adding the reaction mixture into a centrifuge, centrifuging at a centrifugal speed of 10000-11000 rpm for 15-20 minutes, washing the precipitate with water 3-4 times, and vacuum drying at 70-80° C. for 8-9 hours to obtain primary self-assembled zinc oxide; In the primary self-assembly, the mass volume ratio of the coated zinc oxide and the polydimethylallyl ammonium chloride aqueous solution is 22-25 g:1100-1300 mL; The concentration of the polydimethylallyl ammonium chloride aqueous solution is 2 wt %; The secondary self-assembly comprises adding coated zinc oxide and an aqueous solution of sodium dodecylbenzenesulfonate to a reaction kettle, stirring at room temperature at a stirring speed of 400-600 rpm for 30-40 minutes, adding the mixture to a centrifuge, centrifuging at a centrifugal speed of 10,000-11,000 rpm for 15-20 minutes, washing the precipitate with water 3-4 times, and vacuum drying at 70-80° C. for 8-9 hours to obtain secondary self-assembled zinc oxide; In the secondary self-assembly, the mass volume ratio of the coated zinc oxide and the sodium dodecylbenzenesulfonate aqueous solution is 23-26 g: 1100-1300 mL; The concentration of the sodium dodecylbenzenesulfonate aqueous solution is 2wt%; The three-stage self-assembly comprises adding coated zinc oxide and polydimethylallyl ammonium chloride aqueous solution into a reaction kettle, stirring at room temperature at a stirring speed of 400-600 rpm for 30-40 minutes, adding the mixture into a centrifuge, centrifuging at a centrifugal speed of 10000-11000 rpm for 15-20 minutes, washing the precipitate with water 3-4 times, and vacuum drying at 70-80° C. for 8-9 hours to obtain an antibacterial agent; In the three-stage self-assembly, the mass volume ratio of the coated zinc oxide and the polydimethylallyl ammonium chloride aqueous solution is 23-27 g: 1100-1300 mL; The concentration of the polydimethylallyl ammonium chloride aqueous solution is 2 wt %; The polyester chips are pre-crystallized and dried, and then added to a high-speed mixer for high-speed mixing with a flame retardant, an antibacterial agent, a dispersant, an antioxidant, and a pigment, and then added to a twin-screw extruder for melt extrusion and granulation to obtain an antibacterial flame-retardant polyester masterbatch; In the mixture, the mass ratio of polyester chips, flame retardant, antibacterial agent, dispersant, antioxidant and pigment is 65-70:9-10:10-13:1.5-2:0.2-0.3:3.5-4; The polyester chips are one of polyethylene terephthalate, polypropylene terephthalate and polybutylene terephthalate; The dispersant is one of polyethylene wax, polyamide wax and oxidized polyethylene wax; The antioxidant is a compound of a hindered phenol antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and a phosphite antioxidant 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester, wherein the mass ratio of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester to 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester is 1:1; The pigment is one of Pigment Red 122, Pigment Red 48:2, Pigment Blue 15:3, Pigment Violet 23, Pigment Green 7, Pigment Yellow 191, and Pigment Black 7; The aspect ratio of the twin-screw extruder in the melt extrusion is 60:1, and the extrusion temperatures are: the temperature of zone 1 is 260-265°C, the temperature of zone 2 is 265-270°C, the temperature of zone 3 is 270-275°C, the temperature of zone 4 is 275-280°C, the temperature of zone 5 is 280-285°C, the temperature of zone 6 is 285-290°C, and the temperature of zone 7 is 280-285°C.
[0009] An antibacterial flame-retardant polyester masterbatch prepared by the above-mentioned preparation method.
[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention can improve the antibacterial properties of polyester products. The polyester fiber prepared from the antibacterial flame-retardant polyester masterbatch prepared by the present invention can achieve an antibacterial rate of 97.2-97.7% against Escherichia coli, an antibacterial rate of 96.0-96.8% against Staphylococcus aureus, and an antibacterial rate of 94.4-94.9% against Candida albicans. (2) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention can improve the flame retardant properties of polyester products. The limiting oxygen index of polyester fibers prepared from the antibacterial flame-retardant polyester masterbatch prepared by the present invention is 28-32%; (3) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention does not affect the mechanical properties of polyester products. The polyester fiber prepared from the antibacterial flame-retardant polyester masterbatch of the present invention has a breaking strength of 3.71-3.83 cN / dex and an elongation at break of 35.8-36.9%; (4) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention can improve the color fastness of polyester products. The color fastness of polyester fibers prepared from the antibacterial flame-retardant polyester masterbatch prepared by the present invention is level 5; (5) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention, wherein the prepared antibacterial flame-retardant polyester masterbatch has good filtration performance, and the filtration performance is less than 0.3 MPa / g; (6) The method for preparing the antibacterial flame-retardant polyester masterbatch of the present invention can prevent the problem of uneven coloring of polyester products. DETAILED DESCRIPTION
[0011] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described.
[0012] Example 1 A method for preparing an antibacterial flame-retardant polyester masterbatch, specifically comprising: 1. Preparation of flame retardant: (1) Primary coating: 50 g of nano magnesium hydroxide and 2000 mL of water were mixed and added to an ultrasonic oscillator. The mixture was ultrasonically oscillated at 800 W for 20 min at room temperature to obtain a magnesium hydroxide suspension. The entire magnesium hydroxide suspension and 7 g of sodium alginate were then added to a reactor. The mixture was stirred at 70°C at a stirring speed of 300 rpm for 40 min. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 10,000 rpm for 15 min. The precipitate was added to a freeze dryer and freeze-dried at -45°C for 28 h to obtain a primary coated magnesium hydroxide. The particle size of the nano magnesium hydroxide is 100 nm; (2) Secondary coating: 50 g of primary coated magnesium hydroxide and 500 mL of water were mixed and added to an ultrasonic oscillator. The mixture was ultrasonically oscillated at 800 W for 20 min at room temperature to obtain a coated magnesium hydroxide suspension. 1900 mL of a 5 wt% calcium chloride aqueous solution was added to the reactor and stirred at 300 rpm at 20 ° C. At the same time, all the above-mentioned coated magnesium hydroxide suspension was added dropwise to the reactor, and the dropping speed was controlled to be 15 mL / min. After the addition was completed, the mixture was stirred for 3 h. The mixture was added to a centrifuge and centrifuged at 9000 rpm for 15 min. The precipitate was washed with water 3 times, and then added to a vacuum oven and vacuum dried at 70 ° C for 8 h to obtain secondary coated magnesium hydroxide. (3) Adsorption: 30 g of secondary coated magnesium hydroxide and 700 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 400 rpm for 20 min, 400 mL of a 5 wt% aqueous zinc chloride solution was added dropwise at a dropping speed of 25 mL / min. After the addition was completed, stirring was continued for 20 min. The solution was added to a centrifuge and centrifuged at a centrifugal speed of 9000 rpm for 15 min. The precipitate was washed with water 3 times, and then added to a vacuum oven and vacuum dried at 70 ° C for 8 h to obtain adsorbed magnesium hydroxide. (4) Compounding: 32 g of adsorbed magnesium hydroxide and 700 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 400 rpm for 20 min, 580 mL of a 4 wt% methanol solution of 2-methylimidazole was added dropwise at a dropping speed of 25 mL / min. After the addition was completed, an ultrasonic oscillator was added and ultrasonic oscillated at a power of 800 W for 50 min at room temperature. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 8000 rpm for 15 min. The precipitate was washed with water 3 times, and then added to a vacuum oven and vacuum dried at 70 ° C for 8 h to obtain a flame retardant. 2. Preparation of antibacterial agent: (1) Preparation of zinc oxide sol: 26 g of zinc acetate dihydrate and 210 mL of anhydrous ethanol were added to a reactor, stirred at 400 rpm at 70 °C for 40 min, and then 12 mL of ethanolamine was added dropwise at a rate of 2 mL / min. After the addition was completed, stirring was continued for 50 min, and 3 g of polyethylene glycol 400 was added. The mixture was stirred for 2 h to obtain nano zinc oxide sol. (2) Coating: 100 mL of nano zinc oxide sol and 280 mL of a 5 wt% sodium dodecylbenzenesulfonate aqueous solution were mixed and added to an ultrasonic oscillator. Ultrasonic oscillation was performed at room temperature at a power of 500 W for 2.5 h. The mixture was added to a vacuum concentrator and concentrated under reduced pressure at 75 ° C for 25 min. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 10,000 rpm for 15 min. The precipitate was washed with water three times, and then added to a vacuum oven and vacuum dried at 70 ° C for 10 h to obtain coated zinc oxide. (3) Primary self-assembly: 22 g of coated zinc oxide and 1100 mL of a 2 wt% polydimethylallyl ammonium chloride aqueous solution were added to a reactor, stirred at room temperature at 400 rpm for 30 min, placed in a centrifuge, and centrifuged at 10,000 rpm for 15 min. The precipitate was washed three times with water and vacuum dried at 70 °C for 8 h to obtain primary self-assembled zinc oxide. (4) Secondary self-assembly: 23 g of coated zinc oxide and 1100 mL of a 2 wt% aqueous solution of sodium dodecylbenzenesulfonate were added to a reactor, stirred at room temperature at 400 rpm for 30 min, placed in a centrifuge, and centrifuged at 10,000 rpm for 15 min. The precipitate was washed three times with water and vacuum dried at 70 °C for 8 h to obtain secondary self-assembled zinc oxide. (5) Tertiary self-assembly: 23 g of coated zinc oxide and 1100 mL of a 2 wt% polydimethylallyl ammonium chloride aqueous solution were added to a reactor, stirred at 400 rpm for 30 min at room temperature, placed in a centrifuge, and centrifuged at 10,000 rpm for 15 min. The precipitate was washed three times with water and vacuum dried at 70 °C for 8 h to obtain an antibacterial agent. 3. Mixing: After pre-crystallization and drying, the polyester chips are added to a high-speed mixer with flame retardants, antibacterial agents, dispersants, antioxidants, and pigments for high-speed mixing. The chips are then added to a twin-screw extruder for melt extrusion and granulation to obtain antibacterial and flame-retardant polyester masterbatch. The mass ratio of polyester chips, flame retardant, antibacterial agent, dispersant, antioxidant and pigment is 65:9:10:1.5:0.2:3.5; The polyester chips are polyethylene terephthalate; The dispersant is polyethylene wax; The antioxidant is a compound of a hindered phenol antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and a phosphite antioxidant 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester, wherein the mass ratio of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester to 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester is 1:1; The pigment is Pigment Red 122; The aspect ratio of the twin-screw extruder in the melt extrusion is 60:1, and the extrusion temperatures are: the temperature of zone 1 is 260°C, the temperature of zone 2 is 265°C, the temperature of zone 3 is 270°C, the temperature of zone 4 is 275°C, the temperature of zone 5 is 280°C, the temperature of zone 6 is 285°C, and the temperature of zone 7 is 280°C.
[0013] This embodiment also provides an antibacterial flame-retardant polyester masterbatch prepared by the aforementioned preparation method.
[0014] Example 2 A method for preparing an antibacterial flame-retardant polyester masterbatch, specifically comprising: 1. Preparation of flame retardant: (1) Primary coating: 52 g of nano magnesium hydroxide and 2100 mL of water were mixed and added to an ultrasonic oscillator, and ultrasonically oscillated at 800 W for 25 min at room temperature to obtain a magnesium hydroxide suspension; then all of the above magnesium hydroxide suspension and 7.5 g of sodium alginate were added to a reactor, stirred at 75 ° C at a stirring speed of 400 rpm for 45 min, added to a centrifuge, and centrifuged at a centrifugal speed of 10,000 rpm for 18 min. The precipitate was added to a freeze dryer and freeze-dried at -42 ° C for 30 h to obtain a primary coated magnesium hydroxide; The particle size of the nano magnesium hydroxide is 100 nm; (2) Secondary coating: 51 g of primary coated magnesium hydroxide and 520 mL of water were mixed and added to an ultrasonic oscillator. The mixture was ultrasonically oscillated at 800 W for 25 min at room temperature to obtain a coated magnesium hydroxide suspension. 2000 mL of a 5 wt% calcium chloride aqueous solution was added to a reactor and stirred at 30°C at a stirring speed of 400 rpm. At the same time, all the above-mentioned coated magnesium hydroxide suspension was added dropwise to the reactor. The dropping speed was controlled to be 20 mL / min. After the addition was completed, the mixture was stirred for 3.5 h. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 9500 rpm for 18 min. The precipitate was washed with water 3 times. The mixture was then added to a vacuum oven and vacuum dried at 75°C for 9 h to obtain secondary coated magnesium hydroxide. (3) Adsorption: 32 g of secondary coated magnesium hydroxide and 750 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 500 rpm for 25 min, 450 mL of a 5 wt% zinc chloride aqueous solution was added dropwise at a dropping speed of 25 mL / min. After the addition was completed, stirring was continued for 25 min. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 9500 rpm for 15 min. The precipitate was washed with water 3 times, and then added to a vacuum oven and vacuum dried at 75 ° C for 9 h to obtain adsorbed magnesium hydroxide. (4) Compounding: 35 g of adsorbed magnesium hydroxide and 750 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 500 rpm for 25 min, 600 mL of a 4 wt% methanol solution of 2-methylimidazole was added dropwise at a dropping speed of 25 mL / min. After the addition was completed, an ultrasonic oscillator was added and ultrasonic oscillated at a power of 800 W for 55 min at room temperature. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 8500 rpm for 20 min. The precipitate was washed with water three times and then added to a vacuum oven and vacuum dried at 75 ° C for 8.5 h to obtain a flame retardant. 2. Preparation of antibacterial agent: (1) Preparation of zinc oxide sol: 26.5 g zinc acetate dihydrate and 220 mL anhydrous ethanol were added to a reactor, stirred at 72 °C and 500 rpm for 45 min, 13 mL ethanolamine was added dropwise at a rate of 2 mL / min, and stirring was continued for 55 min after the addition was completed. 3.2 g polyethylene glycol 400 was added and stirring was continued for 2 h to obtain nano zinc oxide sol; (2) Coating: 105 mL of nano zinc oxide sol and 290 mL of a 5 wt% sodium dodecylbenzenesulfonate aqueous solution were mixed and added to an ultrasonic oscillator. Ultrasonic oscillation was performed at room temperature at a power of 500 W for 2.5 h. The mixture was added to a vacuum concentrator and concentrated under reduced pressure at 75 ° C for 28 min. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 10,000 rpm for 15 min. The precipitate was washed with water three times and then added to a vacuum oven and vacuum dried at 75 ° C for 10.5 h to obtain coated zinc oxide. (3) Primary self-assembly: 24 g of coated zinc oxide and 1200 mL of a 2 wt% aqueous solution of polydimethylallyl ammonium chloride were added to a reactor, stirred at room temperature at a stirring speed of 500 rpm for 35 min, added to a centrifuge, and centrifuged at a centrifugal speed of 10,000 rpm for 18 min. The precipitate was washed with water three times and vacuum dried at 75 °C for 8.5 h to obtain primary self-assembled zinc oxide; (4) Secondary self-assembly: 24 g of coated zinc oxide and 1200 mL of a 2 wt% aqueous solution of sodium dodecylbenzenesulfonate were added to a reactor, stirred at room temperature at a stirring speed of 500 rpm for 35 min, added to a centrifuge, and centrifuged at a centrifugal speed of 10,000 rpm for 18 min. The precipitate was washed with water three times and vacuum dried at 75 °C for 8.5 h to obtain secondary self-assembled zinc oxide; (5) Tertiary self-assembly: 25 g of coated zinc oxide and 1200 mL of a 2 wt% polydimethylallyl ammonium chloride aqueous solution were added to a reactor, stirred at room temperature at a stirring speed of 500 rpm for 35 min, added to a centrifuge, and centrifuged at a centrifugal speed of 10,000 rpm for 18 min. The precipitate was washed with water three times and vacuum dried at 75 °C for 8.5 h to obtain an antibacterial agent. 3. Mixing: After pre-crystallization and drying, the polyester chips are added to a high-speed mixer with flame retardants, antibacterial agents, dispersants, antioxidants, and pigments for high-speed mixing. The chips are then added to a twin-screw extruder for melt extrusion and granulation to obtain antibacterial and flame-retardant polyester masterbatch. The mass ratio of polyester chips, flame retardant, antibacterial agent, dispersant, antioxidant and pigment is 68:9.5:12:1.7:0.2:3.8; The polyester chips are polytrimethylene terephthalate; The dispersant is polyamide wax; The antioxidant is a compound of a hindered phenol antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and a phosphite antioxidant 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester, wherein the mass ratio of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester to 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester is 1:1; The pigment is Pigment Red 48:2; The aspect ratio of the twin-screw extruder in the melt extrusion is 60:1, and the extrusion temperatures are: the temperature of zone 1 is 260°C, the temperature of zone 2 is 265°C, the temperature of zone 3 is 270°C, the temperature of zone 4 is 275°C, the temperature of zone 5 is 280°C, the temperature of zone 6 is 285°C, and the temperature of zone 7 is 280°C.
[0015] This embodiment also provides an antibacterial flame-retardant polyester masterbatch prepared by the aforementioned preparation method.
[0016] Example 3 A method for preparing an antibacterial flame-retardant polyester masterbatch, specifically comprising: 1. Preparation of flame retardant: (1) Primary coating: 55 g of nano magnesium hydroxide and 2200 mL of water were mixed and added to an ultrasonic oscillator, and ultrasonically oscillated at 800 W for 30 min at room temperature to obtain a magnesium hydroxide suspension; then all of the above magnesium hydroxide suspension and 8 g of sodium alginate were added to a reactor, stirred at 80°C at a stirring speed of 500 rpm for 50 min, added to a centrifuge, and centrifuged at a centrifugal speed of 11000 rpm for 20 min. The precipitate was added to a freeze dryer and freeze-dried at -40°C for 32 h to obtain a primary coated magnesium hydroxide; The particle size of the nano magnesium hydroxide is 100 nm; (2) Secondary coating: 52 g of primary coated magnesium hydroxide and 550 mL of water were mixed and added to an ultrasonic oscillator. The mixture was ultrasonically oscillated at 800 W for 30 min at room temperature to obtain a coated magnesium hydroxide suspension. 2100 mL of a 5 wt% calcium chloride aqueous solution was added to a reactor and stirred at 40 ° C at a stirring speed of 500 rpm. At the same time, all the above-mentioned coated magnesium hydroxide suspension was added dropwise to the reactor, and the dropping speed was controlled to 20 mL / min. After the addition was completed, the mixture was stirred for 4 h. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 10,000 rpm for 20 min. The precipitate was washed with water 4 times, and then added to a vacuum oven and vacuum dried at 80 ° C for 10 h to obtain secondary coated magnesium hydroxide. (3) Adsorption: 35 g of secondary coated magnesium hydroxide and 800 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 600 rpm for 30 min, 500 mL of a 5 wt% aqueous zinc chloride solution was added dropwise at a dropping speed of 30 mL / min. After the addition was completed, stirring was continued for 30 min. The solution was added to a centrifuge and centrifuged at a centrifugal speed of 10,000 rpm for 20 min. The precipitate was washed with water 4 times, and then added to a vacuum oven and vacuum dried at 80 ° C for 10 h to obtain adsorbed magnesium hydroxide. (4) Compounding: 36 g of adsorbed magnesium hydroxide and 800 mL of water were added to a reactor. After stirring at room temperature at a stirring speed of 600 rpm for 30 min, 640 mL of a 4 wt% methanol solution of 2-methylimidazole was added dropwise at a dropping speed of 30 mL / min. After the addition was completed, an ultrasonic oscillator was added and ultrasonic oscillated at a power of 800 W for 60 min at room temperature. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 9000 rpm for 20 min. The precipitate was washed with water 4 times, and then added to a vacuum oven and vacuum dried at 80 ° C for 9 h to obtain a flame retardant. 2. Preparation of antibacterial agent: (1) Preparation of zinc oxide sol: 27 g zinc acetate dihydrate and 230 mL anhydrous ethanol were added to a reactor, stirred at 75 °C and 600 rpm for 50 min, and then 14 mL ethanolamine was added dropwise at a rate of 3 mL / min. After the addition was completed, stirring was continued for 60 min, and 3.5 g polyethylene glycol 400 was added and stirring was continued for 2.5 h to obtain nano zinc oxide sol; (2) Coating: 110 mL of nano zinc oxide sol and 300 mL of a 5 wt% sodium dodecylbenzenesulfonate aqueous solution were mixed and added to an ultrasonic oscillator. Ultrasonic oscillation was performed at room temperature at a power of 500 W for 3 h. The mixture was added to a vacuum concentrator and concentrated at 80 ° C for 30 min. The mixture was added to a centrifuge and centrifuged at a centrifugal speed of 11,000 rpm for 20 min. The precipitate was washed with water 4 times, and then added to a vacuum oven and vacuum dried at 80 ° C for 11 h to obtain coated zinc oxide. (3) Primary self-assembly: 25 g of coated zinc oxide and 1300 mL of a 2 wt% polydimethylallyl ammonium chloride aqueous solution were added to a reactor, stirred at room temperature at a stirring speed of 600 rpm for 40 min, added to a centrifuge, and centrifuged at a centrifugal speed of 11000 rpm for 20 min. The precipitate was washed with water four times and vacuum dried at 80 °C for 9 h to obtain primary self-assembled zinc oxide; (4) Secondary self-assembly: 26 g of coated zinc oxide and 1300 mL of a 2 wt% sodium dodecylbenzenesulfonate aqueous solution were added to a reactor, stirred at room temperature at a stirring speed of 600 rpm for 40 min, added to a centrifuge, and centrifuged at a centrifugal speed of 11000 rpm for 20 min. The precipitate was washed with water four times and vacuum dried at 80 °C for 9 h to obtain secondary self-assembled zinc oxide; (5) Tertiary self-assembly: 27 g of coated zinc oxide and 1300 mL of a 2 wt% polydimethylallyl ammonium chloride aqueous solution were added to a reactor, stirred at room temperature at a stirring speed of 600 rpm for 40 min, added to a centrifuge, and centrifuged at a centrifugal speed of 11000 rpm for 20 min. The precipitate was washed with water four times and vacuum dried at 80 °C for 9 h to obtain an antibacterial agent. 3. Mixing: After pre-crystallization and drying, the polyester chips are added to a high-speed mixer with flame retardants, antibacterial agents, dispersants, antioxidants, and pigments for high-speed mixing. The chips are then added to a twin-screw extruder for melt extrusion and granulation to obtain antibacterial and flame-retardant polyester masterbatch. The mass ratio of polyester chips, flame retardant, antibacterial agent, dispersant, antioxidant and pigment is 70:10:13:2:0.3:4; The polyester chips are polybutylene terephthalate; The dispersant is oxidized polyethylene wax; The antioxidant is a compound of a hindered phenol antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester and a phosphite antioxidant 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester, wherein the mass ratio of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester to 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester is 1:1; The pigment is Pigment Blue 15:3; The aspect ratio of the twin-screw extruder in the melt extrusion is 60:1, and the extrusion temperatures are: the temperature of zone 1 is 265°C, the temperature of zone 2 is 270°C, the temperature of zone 3 is 275°C, the temperature of zone 4 is 280°C, the temperature of zone 5 is 285°C, the temperature of zone 6 is 290°C, and the temperature of zone 7 is 285°C.
[0017] This embodiment also provides an antibacterial flame-retardant polyester masterbatch prepared by the aforementioned preparation method.
[0018] Comparative Example 1 On the basis of Example 2, the first step of preparing the flame retardant was omitted, and in the third mixing step, an equal amount of nano magnesium hydroxide with a particle size of 100 nm was used to replace the flame retardant.
[0019] Comparative Example 2 On the basis of Example 2, the second step of preparing the antibacterial agent was omitted, and in the third mixing step, an equal amount of nano zinc oxide with a particle size of 100 nm was used to replace the addition of the antibacterial agent.
[0020] Test Example 1 The antibacterial flame-retardant polyester masterbatches prepared in Examples 1-3 and Comparative Examples 1-2 were used to prepare polyester fibers, respectively. The specific preparation methods are as follows: The polyester chips are pre-crystallized and dried, and then mixed with antibacterial flame-retardant polyester masterbatch in a high-speed mixer, and then added to a twin-screw extruder for melt extrusion, and then added to a melt filter for filtration, and then added to a spinning machine for spinning, and then cooled, oiled, and wound at high speed to produce polyester fibers; Among them, the mass ratio of polyester chips to antibacterial masterbatch is 95:5; The temperature during the melt extrusion is 280°C; The filter screen accuracy during the filtration is 50 mesh; The spinning temperature during the spinning is 270°C; The antibacterial polyester fiber is 1.5 dtex.
[0021] The limiting oxygen index, breaking strength, breaking elongation, and color fastness of the polyester fibers prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the presence of uneven coloring in the polyester fibers was observed. The test and observation results are as follows:
[0022] The obtained polyester fibers were then woven into 200mm×200mm polyester fiber fabrics. The antibacterial properties of the polyester fiber fabrics against Escherichia coli, Staphylococcus aureus, and Candida albicans were tested according to the GB / T20944-2007 test standard. The test results are as follows:
[0023] Test Example 2 The filtration performance of the polyester masterbatch prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test results are as follows:
[0024] It can be seen from the above results that by adding flame retardants and antibacterial agents to the mixture, the filtration performance of the polyester masterbatch is slightly affected; the limiting oxygen index, antibacterial properties and color fastness of the polyester fiber made from the polyester masterbatch can be improved, and the problem of uneven coloring can be avoided; and the breaking strength and elongation at break are slightly affected.
[0025] When preparing the flame retardant, sodium alginate is first used to perform primary coating on nano-magnesium hydroxide, and then calcium chloride is used to perform secondary coating. During the secondary coating, the calcium chloride cross-links the sodium alginate to form a calcium alginate cross-linked layer on the surface of the nano-magnesium hydroxide. Then, zinc ions are adsorbed during adsorption. The calcium alginate cross-linked layer can improve the flame retardancy of the magnesium hydroxide and the adsorption effect on zinc ions. Finally, 2-methylimidazole is used for compounding, and ultrasonic oscillation is used to promote the compounding to form ZIF-8, thereby obtaining a flame retardant with magnesium hydroxide as the core, a calcium alginate cross-linked layer as the middle layer, and a ZIF-8 as the outer layer. The magnesium hydroxide, the calcium alginate cross-linked layer, and the ZIF-8 cooperate with each other to improve the flame retardant effect and the fixation effect on the pigment. The presence of ZIF-8 also reduces the water absorption of the calcium alginate cross-linked layer, thereby improving the dispersibility of the flame retardant and the compatibility with polyester. When preparing the antibacterial agent, firstly, a small-particle, transparent zinc oxide sol is prepared, then anionic sodium dodecylbenzenesulfonate is used for coating, then cationic polydimethylallyl ammonium chloride is used for self-assembly, then anionic sodium dodecylbenzenesulfonate is used for self-assembly, and finally cationic polydimethylallyl ammonium chloride is used for self-assembly, thereby coating the surface of the zinc oxide sol with multiple layers of polydimethylallyl ammonium chloride having antibacterial effect, thereby improving the antibacterial performance of the antibacterial agent while improving the dispersibility of the antibacterial agent, the compatibility with polyester and the fixation effect on the pigment.
[0026] Unless otherwise specified, all percentages used in the present invention are by mass.
[0027] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for preparing an antibacterial flame-retardant polyester masterbatch, characterized in that: The method comprises the following steps: preparing a flame retardant, preparing an antibacterial agent, and mixing materials; The flame retardant preparation comprises the following steps: primary coating, secondary coating, adsorption, and compounding; In the first-stage coating, nano magnesium hydroxide and water are mixed evenly to obtain a magnesium hydroxide suspension; then mixed with sodium alginate, stirred at 70-80° C., centrifuged, and the precipitate is freeze-dried to obtain a first-stage coated magnesium hydroxide; The secondary coating comprises mixing the primary coated magnesium hydroxide and water evenly to obtain a coated magnesium hydroxide suspension; stirring the calcium chloride aqueous solution at 20-40° C., while dripping the coated magnesium hydroxide suspension into the calcium chloride aqueous solution, continuing to stir after the dripping, centrifuging, washing, and vacuum drying the precipitate to obtain the secondary coated magnesium hydroxide; The adsorption comprises mixing the secondary coated magnesium hydroxide and water at room temperature and stirring, adding a zinc chloride aqueous solution dropwise, continuing stirring after the addition is completed, centrifuging, washing, and vacuum drying the precipitate to obtain adsorbed magnesium hydroxide; The composite comprises mixing the adsorbed magnesium hydroxide and water, stirring at room temperature, adding a methanol solution of 2-methylimidazole dropwise, and mixing evenly, centrifuging, washing, and vacuum drying the precipitate to obtain a flame retardant; The method for preparing the antibacterial agent comprises the following steps: preparing zinc oxide sol, coating, primary self-assembly, secondary self-assembly, and tertiary self-assembly; The method for preparing the zinc oxide sol comprises mixing zinc acetate dihydrate and anhydrous ethanol, stirring at 70-75° C., dropping ethanolamine, continuing stirring after the dropping, adding polyethylene glycol 400, and continuing stirring to obtain a nano zinc oxide sol; The coating comprises mixing the nano zinc oxide sol and the sodium dodecylbenzene sulfonate aqueous solution uniformly, concentrating under reduced pressure, centrifuging, washing, and vacuum drying the precipitate to obtain coated zinc oxide; The primary self-assembly comprises adding coated zinc oxide and polydimethylallyl ammonium chloride aqueous solution into a reaction kettle, stirring at room temperature, centrifuging, washing, and vacuum drying the precipitate to obtain primary self-assembled zinc oxide; The secondary self-assembly comprises mixing the coated zinc oxide and the sodium dodecylbenzene sulfonate aqueous solution, stirring at room temperature, centrifuging, washing, and vacuum drying the precipitate to obtain the secondary self-assembled zinc oxide; In the three-stage self-assembly, the coated zinc oxide and the polydimethylallyl ammonium chloride aqueous solution are mixed, stirred at room temperature, centrifuged, and the precipitate is washed and vacuum dried to obtain the antibacterial agent.
2. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the primary coating, the mass volume ratio of nano magnesium hydroxide, water and sodium alginate is 50-55g:2000-2200mL:7-8g; The particle size of the nano magnesium hydroxide is 100 nm.
3. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the secondary coating, the mass volume ratio of the primary coating magnesium hydroxide, water, and calcium chloride aqueous solution is 50-52g:500-520mL:1900-2100mL; The concentration of the calcium chloride aqueous solution is 5wt%; The dropping speed of the calcium chloride aqueous solution is 15-20 mL / min.
4. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the adsorption, the mass volume ratio of the secondary coated magnesium hydroxide, water, and zinc chloride aqueous solution is 30-35 g:700-800 mL:400-500 mL; The concentration of the zinc chloride aqueous solution is 5wt%; The dropping speed of the zinc chloride aqueous solution is 25-30 mL / min.
5. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the composite, 32-36 g: 700-800 mL: 580-640 mL of magnesium hydroxide, water, and a methanol solution of 2-methylimidazole with a concentration of 4 wt % are adsorbed; The concentration of the methanol solution of 2-methylimidazole is 4wt%; The dropping speed of the methanol solution of 2-methylimidazole is 25-30 mL / min.
6. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the preparation of the zinc oxide sol, the mass volume ratio of zinc acetate dihydrate, anhydrous ethanol, ethanolamine, and polyethylene glycol 400 is 26-27 g: 210-230 mL: 12-14 mL: 3-3.5 g; The dropping speed of the ethanolamine is 2-3 mL / min; In the coating, the volume ratio of nano zinc oxide sol and sodium dodecylbenzene sulfonate aqueous solution is 100-110:280-300; The concentration of the sodium dodecylbenzenesulfonate aqueous solution is 5 wt %.
7. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: In the primary self-assembly, the mass volume ratio of the coated zinc oxide and the polydimethylallyl ammonium chloride aqueous solution is 22-25 g: 1100-1300 mL; The concentration of the polydimethylallyl ammonium chloride aqueous solution is 2wt%; In the secondary self-assembly, the mass volume ratio of the coated zinc oxide and the sodium dodecylbenzene sulfonate aqueous solution is 23-26 g: 1100-1300 mL; The concentration of the sodium dodecylbenzenesulfonate aqueous solution is 2wt%; In the three-stage self-assembly, the mass volume ratio of the coated zinc oxide and the polydimethylallyl ammonium chloride aqueous solution is 23-27 g: 1100-1300 mL; The concentration of the polydimethylallyl ammonium chloride aqueous solution is 2 wt %.
8. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 1, characterized in that: The mixed material is prepared by pre-crystallizing and drying the polyester chips, adding the flame retardant, antibacterial agent, dispersant, antioxidant and pigment into a high-speed mixer for high-speed mixing, and then adding the mixture into a twin-screw extruder for melt extrusion and granulation to obtain antibacterial flame-retardant polyester masterbatch.
9. The method for preparing the antibacterial flame-retardant polyester masterbatch according to claim 8, characterized in that: In the mixture, the mass ratio of polyester chips, flame retardant, antibacterial agent, dispersant, antioxidant and pigment is 65-70:9-10:10-13:1.5-2:0.2-0.3:3.5-4; The polyester slice is one of polyethylene terephthalate, polypropylene terephthalate and polybutylene terephthalate; The dispersant is one of polyethylene wax, polyamide wax and oxidized polyethylene wax; The antioxidant is a compound of a hindered phenol antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester and a phosphite antioxidant 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester, wherein the mass ratio of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester to 3,5-di-tert-butyl-4-hydroxybenzoic acid octyl ester is 1:1; The pigment is one of Pigment Red 122, Pigment Red 48:2, Pigment Blue 15:3, Pigment Violet 23, Pigment Green 7, Pigment Yellow 191, and Pigment Black 7; The aspect ratio of the twin-screw extruder in the melt extrusion is 60:1, and the extrusion temperatures are: the temperature of zone 1 is 260-265°C, the temperature of zone 2 is 265-270°C, the temperature of zone 3 is 270-275°C, the temperature of zone 4 is 275-280°C, the temperature of zone 5 is 280-285°C, the temperature of zone 6 is 285-290°C, and the temperature of zone 7 is 280-285°C.
10. An antibacterial flame-retardant polyester masterbatch prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Flame-retardant polyester fiber and preparation method thereof
CN120158836A
High-flame-retardant low-smoke halogen-free cable sheath material and preparation method thereof
CN121699271A